Formulasi dan Uji Stabilitas Sediaan Lip Balm Mengandung Ekstrak Aloe vera (Aloe barbadensis Miller) - Fujiningrum, Anggi Lyia; Putri, Arryrawanda Bunga Priswanto; Achnanda, Anisa' Fitri Mulya; Ershana, Aprisia Aji Kartika (Jurnal Global Ilmiah, 2025)
Lips are a very sensitive part of the skin and easily dry out because they do not have sebaceous glands. One common solution used to maintain lip moisture is lip balm. However, most commercial lip balms still contain synthetic ingredients that can cause irritation. Aloe vera is known to have moisturizing, anti-inflammatory, and antioxidant effects that have the potential to be applied in natural lip balm formulations. This study aims to formulate and evaluate the physical characteristics and stability of lip balms with the addition of Aloe vera extract in various concentrations. Lip balm formulations were carried out in three variations: without Aloe vera (F1), with 6% Aloe vera (F2), and 8% (F3). Evaluations included organoleptic tests (color, odor, texture), homogeneity, pH, melting point, and temperature stability during two weeks of storage. All preparations had a yellowish-white color, a solid texture, and a distinctive rose aroma. F1 showed the highest pH (7.2), a melting point of 50°C, and excellent physical stability without changes during storage. F2 had the pH most in line with BPOM standards (6.6), a melting point of 51°C, and showed slight oil separation that was still tolerable. F3 had a pH of 6.2 and the highest melting point (52°C), but experienced more significant oil separation during storage. Different from previous studies that combined Aloe vera with natural or synthetic dyes, this study prioritizes a clean beauty approach based on food-grade ingredients that are safe and skin-friendly. Formula F2 was considered the most optimal because it showed the best balance between physical stability, pH compatibility, and moisturizing effectiveness of Aloe vera, making it a superior candidate as a natural lip balm that is safe, effective, and in line with modern consumer preferences.